If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -26 = -3t + 8 Reorder the terms: -26 = 8 + -3t Solving -26 = 8 + -3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '3t' to each side of the equation. -26 + 3t = 8 + -3t + 3t Combine like terms: -3t + 3t = 0 -26 + 3t = 8 + 0 -26 + 3t = 8 Add '26' to each side of the equation. -26 + 26 + 3t = 8 + 26 Combine like terms: -26 + 26 = 0 0 + 3t = 8 + 26 3t = 8 + 26 Combine like terms: 8 + 26 = 34 3t = 34 Divide each side by '3'. t = 11.33333333 Simplifying t = 11.33333333
| 2*ln(x)-ln(5)=ln(2) | | 3xy(z-5)+4m(5-z)=0 | | x-2(18/4)=3 | | 7y^2(x-5)-5(x-5)=0 | | -2a^2+19=-21 | | 3x+4=3(x+1)+1 | | T(n)=4n+2 | | 2x-xsquared+16=0 | | 3x+4=3(x+1) | | -2a+19=-21 | | 10v^2+33v-7=0 | | 10x^2=-7+5x | | n/3-9=6 | | 3x-18+8x+1=x | | 4x+7i=-7+8yi | | W-15/w^2-5w-6 | | 407+111x=1850 | | x^2-56=-10x | | x^2-5=40 | | 4-2n-2=-2 | | B+11b+30=0 | | 7=x^2-9 | | y=x-(-4) | | v^2-7=6v | | 0=-16m | | (4p-33)/(-2p-33) | | -5(x+2)=3-5x | | (a^2-4a+6)+(3a^2+13a+1)= | | 6(5z-1)-4(z+6)=17(z+1) | | (a^2-4a+6)+(3a^2+13a+6)= | | e^3=2x-5 | | ((-2)/7)x=6 |